Ways local Internet Service Providers can better meet consumers' needs. - Seow, Yunn Shyan. (2008)
This project seeks to explore the ways local ISPs can better meet Customers' needs. We aim to identify the significant factors that customers look for when choosing an ISP, to determine the factors that affect their satisfaction level of services provided by the ISPs and to recommend strategies that ISPs should adopt in order to stay competitive in the future.